2017
DOI: 10.5114/aoms.2017.65649
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values of Notch signalling in renal carcinoma

Abstract: IntroductionNotch signalling, an evolutionarily conserved mechanism of cellular differentiation and tissue remodelling, is frequently deregulated in several human malignancies, including renal cell carcinoma (RCC). However, the prognostic value of individual Notch pathway members in RC subtypes remains indefinable. The present study investigates whether the differential expression of Notch members has a contrary effect on disease-free survival (DFS) in clear cell renal cell carcinoma (KIRC), papillary cell ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Nevertheless, long-term outcomes are still not satisfactory, particularly due to common local recurrences, distal metastases and limited drug response [6]. Under those circumstances, an improvement in RCC patients' management could be obtained by developing novel, easily obtainable and cheap prognostic markers which might help select patients who would benefit most from additional postoperative care [7,8]. It is commonly known that blood is full of tumor-associated biomarkers, such as pro-inflammatory cells, including neutrophils and platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, long-term outcomes are still not satisfactory, particularly due to common local recurrences, distal metastases and limited drug response [6]. Under those circumstances, an improvement in RCC patients' management could be obtained by developing novel, easily obtainable and cheap prognostic markers which might help select patients who would benefit most from additional postoperative care [7,8]. It is commonly known that blood is full of tumor-associated biomarkers, such as pro-inflammatory cells, including neutrophils and platelets.…”
Section: Introductionmentioning
confidence: 99%
“…According to Abrahamsen et al, invasive diagnostics are not necessary in patients with mild UA, and attentive observation is sufficient [13]. For now, it seems that research in patients with UA on the role of disorders related to notch signaling or long chain non-coding RNA is the future in prevention, prognosis or treatment, as is the case of many age-related diseases, including hematological malignancies and other cancers [26][27][28]. In our study however, during a 3-year follow-up, significantly more deaths were noted in the group with UA than in the group without anemia, even though the anemia was mild in most of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that their levels were overly expressed in head and neck squamous cell carcinoma (HNSCC), suggesting their tumourigenic roles (as oncogenes). Recently the predictive value of Notch signalling in renal carcinoma patients has been suggested [61]. Their association with cancer was first demonstrated long before this in T-cell acute lymphoblastic leukaemia [59,62].…”
Section: Notch Proteinsmentioning
confidence: 99%